Decompressive effects of draining tube on suppurative and sclerosing osteomyelitis in the jaw - Buyanbileg Sodnom-Ish; Mi Young Eo; Mi Hyun Seo; Jong Ho Lee; Soung Min Kim (BMC Musculoskeletal Disorders, 2021)
Abstract Background Osteomyelitis (OM) in the jaw is an inflammatory disease of osseous tissue that begins in the medullary space and progressively expands to the cortical portion of the bone, the Haversian system, the periosteum and the overlying soft tissue. Despite advances in dental and medical care, OM persists and is of important concern in modern medicine. Active negative pressure is known to prevent post-operative hematoma; decrease the number of bacterial pathogens, accumulation of toxins, and necrotic tissue; and promote osteogenesis and angiogenesis with the use of a draining tube such as the Jackson-Pratt (JP) or Hemovac. The purpose of this study was to assess the effectiveness of decompression for the treatment of OM in the jaw. Methods This retrospective study included a total of 130 patients, 55 patients with sclerosing OM and 75 patients with suppurative OM were included. The radiographic bone densities expressed as a grayscale values (GSVs), were measured using an easy digitalized panoramic analysis (EDPA) method, processed on the conditional inference tree, generated by the R program® 3.2.3 with a probability of 96.8%. Rectangle annotation analysis of INFINITT PACS® (INFINITT Healthcare, Seoul, Korea) of 50 mm2 was determined as the region of interest (ROI). Student’s t-test and ANOVA were used to determine significance (p < 0.05). Results Significant changes was observed between radiographic bone density in the sclerosing type with drain and without drain at the six-month and one-year follow-up (p < 0.05). Significant difference was demonstrated between the suppurative OM with drain and without drain groups at the one-year follow-up (p < 0.05). Conclusion The OM groups with drain exhibited more enhanced bone density compared to the groups without drain at the six-month and one-year follow-ups. The drain insertion for decompression is effective for the management of sclerosing and suppurative OM. It is recommended to implement it for the management of OM.